Analisis Kebutuhan Pengembangan Media Pembelajaran Berbasis Augmented Reality Pada Matakuliah Rangkaian Listrik - Luthfi, Afdal; Muskhir, Mukhlidi; Jalinus, Nizwardi; Sukardi, Sukardi; Effendi, Hansi (Jurnal Pendidikan Teknik Elektro, 2024)
In the rapidly evolving digital era, the transformation of learning media has revolutionized the education system by providing innovative ways of material delivery and learner interaction with learning content. In particular, Augmented Reality (AR) technology has shown its potential to enrich the learning experience in an interactive and engaging way. The main objective of this research is to analyze the current learning conditions and evaluate the effectiveness of using AR as a learning medium. The methods used include interviews with lecturers and student needs surveys using questionnaires. Results from interviews and surveys indicated that many students have difficulty in understanding the material, and conventional learning media such as whiteboards and PowerPoint have not been effective enough in presenting complex concepts intuitively. The discussion of this research reveals that AR can be an important solution in clarifying the visualization of Electrical Circuit concepts, allowing students to virtually see and interact with complex circuit components. With AR, students can modify variables and immediately see the effect on the circuit, which deepens their understanding of the material being taught. It also supports independent learning outside the classroom, as AR can be accessed through personal devices such as smartphones. The conclusion of this study shows that the integration of AR in learning Electrical Circuits can improve students' understanding and interest in learning. Recommendations given based on this research are the development of more interactive and integrative AR-based learning content, accompanied by lecturer training to maximize the potential of this technology in education. The implementation of AR will not only improve the quality of learning but also prepare students with relevant skills for the future.